High cell density production of multimethyl-branched long-chain esters in Escherichia coli and determination of their physicochemical properties - Menendez-Bravo, Simón Matías (2016)
Background: Microbial synthesis of oleochemicals derived from native fatty acid (FA) metabolism has presented significant advances in recent years. Even so, native FA biosynthetic pathways often provide a narrow variety of usually linear hydrocarbons, thus yielding end products with limited structural diversity. To overcome this limitation, we took advantage of a polyketide synthase-based system from Mycobacterium tuberculosis and developed an Escherichia coli platform with the capacity to synthesize multimethyl-branched long-chain esters (MBE) with novel chemical structures. Results: With the aim to initiate the characterization of these novel waxy compounds, here, we describe the chassis optimization of the MBE producer E. coli strain for an up-scaled oil production. By carrying out systematic metabolic engineering, we improved the final titer to 138.1 ± 5.3 mg MBE L-1 in batch cultures. Fed-batch microbial fermentation process was also optimized achieving a maximum yield of 790.2 ± 6.9 mg MBE L-1 with a volumetric productivity of 15.8 ± 1.1 mg MBE (L h)-1. Purified MBE oil was subjected to various physicochemical analyses, including differential scanning calorimetry (DSC) and pressurized-differential scanning calorimetry (P-DSC) studies. Conclusions: The analysis of the pour point, DSC, and P-DSC data obtained showed that bacterial MBE possess improved cold flow properties than several plant oils and some chemically modified derivatives, while exhibiting high oxidation stability at elevated temperatures. These encouraging data indicate that the presence of multiple methyl branches in these novel esters, indeed, conferred favorable properties which are superior to those of linear esters.